The legacy of HfrH: Mutations in the two-component system CreBC are responsible for the unusual phenotype of an Escherichia coli arcA mutant - Nikel, P.I. (2008)
Strains derived from HfrH carrying the arcA2 null mutation exhibit a higher respiratory rate, enhanced glucose consumption, and a more-reduced intracellular redox state than arcA deletion mutants of a different lineage. The phenotype of the arcA2 mutants was due to the presence of a creC constitutive mutation introduced by P1 transduction. Copyright © 2008, American Society for Microbiology. All Rights Reserved.